The analytic hierarchy process in transportation sector - Islam, Rafikul; Saaty, Thomas (Springer, 2010)
The Analytic Hierarchy Process (AHP) is a well-known multi-criteria decision making method that has been applied to solve problems in diverse areas. The present paper deals with applications of the AHP in the transportation sector. We describe three applications of the AHP namely, (1) A governmental agency with jurisdiction over a certain area must decide on whether to build or not to build a bridge or a tunnel across a river presently served by a privately owned ferry. The factors or control criteria which affect both the benefits and costs of crossing a river are given in two hierarchies that fall into three categories: economic, social, and environmental. The decision is made in terms of the ratios of the priorities of the alternatives from the benefits hierarchy to those from the costs hierarchy although the AHP also has a second way to synthesize benefits and costs involving strategic criteria not used in this example. (2) In planning alternative strategies for the future of the Sudan's transport system, the method of anticipatory scenario construction was used. The construction of the composite scenario was based on the use of the method of priorities to compare the individual scenarios as to their feasibility and desirability to the various forces which will shape changes in Sudanese society. (3) Here we apply the dependence with a feedback system in making a decision to buy a car made by an American, a European, or a Japanese company on the basis of three criteria: cost, repair, and durability.